Congress volume : Cambridge, 1995 - Emerton, John Adney. (Supplements to Vetus Testamentum, 1997)
This volume publishes the papers given by invitation at the fifteenth Congress of the International Organization for the Study of the Old Testament, which was held at Cambridge in July 1995, under the Presidency of J.A. Emerton. The articles cover a wide range of subjects relevant to the study of the Old Testament, and reflect the ongoing debate on a variety of themes among the world's leading contemporary Old Testament scholars.